Neither Backlash nor Convergence: Dynamics of Intracouple Childcare Division after the First Covid-19 Lockdown and Subsequent Reopening in Germany - Christina Boll; Dana Müller; Simone Schüller (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Using unique monthly panel data from the Institute for Employment Research (IAB) covering the immediate postlockdown period from June to August 2020, we investigate the opposing claims of widening/closing the gender gap in parental childcare during the COVID-19 pandemic in Germany. We contribute to the current literature by analyzing the medium-term dynamics of couples' childcare division and by considering the prepandemic division rather than providing merely snapshots during lockdown. Our results suggest a slight shift toward a more egalitarian division in June that, however, faded out in subsequent months. Starting from a fairly “traditional” prepandemic childcare division, the lockdown stimulus was not nearly strong enough to level the playing field. A subgroup analysis differentiating between parents' individual lockdown-specific work arrangements shows that the drivers of the observed shift were mothers who worked more than 20 hours a week and for whom remote work was not possible. Fathers' work arrangement instead did not play a significant role. We conclude that the shift emerged out of necessity rather than opportunity, which makes it likely to fade once the necessity vanishes, thereby catapulting parents back to their initial childcare arrangements.
Keywords: D13; J13; J16; 330; Covid-19; intracouple division of unpaid work; childcare; gender; working from home; IAB-HOPP